Perception on e-invoice implementation among small and medium-sizes enterprises in Sik, Kedah - Siti Nur Aishah, Ishak (2024)
Malaysia's journey towards digitalization is guided by the 12th Malaysia Plan which is aiming for a digital economy contribution of at least 25.5% to GDP by 2025. This plan highlights Malaysia's commitment to integrating digital technologies across sectors such as education, healthcare, agriculture, and manufacturing. The e-Invoice initiative is expected to modernize business practices, digitize invoicing processes and improve interactions between businesses and government agencies. It also aims to enhance efficiency, streamline operations, increase tax compliance, and reduce errors by enabling near real-time validations. However, there is limited research on perception on e-Invoice implementation among SMEs. Therefore, this study aims to investigate the level of attitudes, subjective norms, perceived behavioural control, perceived usefulness, perceived ease of use, intention of user and perceptions on e- Invoice implementation among SMEs in Sik, Kedah by using the variables Theory of Planned Behavior and Technology Acceptance Model. Data collection was conducted through an online survey distributed via Google Forms and social media platforms which resulted in 72 usable responses from an initial sample of 118 SMEs. The analysis was performed using the Statistical Package for the Social Sciences (SPSS). The results indicate that all variables fall within the range of 3.41 to 4.20 which reflects a high perception. This demonstrates that respondents generally hold positive views regarding perceptions on e-Invoice implementation among SMEs in Sik, Kedah. This study provides valuable insights for policymakers and SME practitioners to enhance the adoption of e-Invoice systems which could contributing to the broader goals of digital transformation and economic development in Malaysia